The Influence of Financial Knowledge on Financial Planning Through Financial Strategy as a Mediating Variable A Study on School of Communication and Business Students, Telkom University - Mustafa, Syah Jehan Afid; Kurnianingrum, Dian; Fakhri, Mahendra; Kartawinata, Budi Rustandi; Dzakiy, Uruqul Nadhif; Akbar, Aldi (Journal of Ecohumanism, 2024)
This study explores the significance of financial knowledge among students, specifically its impact on understanding financial behavior. It focuses on the relationship between Financial Knowledge and Financial Planning, with Financial Strategy acting as a mediating variable. Employing a quantitative descriptive research design, the research sample consists of 100 students from the Faculty of Communication and Business at Telkom University. Data analysis was conducted using path analysis and hypothesis testing through Smart PLS 4.0 software. The findings reveal a significant influence of Financial Knowledge (X) on Financial Planning (Y). Additionally, Financial Knowledge (X) positively impacts Financial Strategy (Z), which in turn significantly affects Financial Planning (Y). Ultimately, the results demonstrate that Financial Knowledge (X) significantly influences Financial Planning (Y), both directly and indirectly through Financial Strategy (Z). These findings underscore the crucial role of financial knowledge in enhancing financial planning among students.